2011
DOI: 10.1051/epjap/2011110017
|View full text |Cite
|
Sign up to set email alerts
|

Turbid medium polarimetry in biomedical imaging and diagnosis

Abstract: Abstract. Studies on polarization properties of scattered light from a random medium like biological tissue have received considerable attention because polarization can be used as an effective tool to discriminate against multiply scattered light (acting as a gating mechanism) and thus can facilitate high resolution imaging through tissue. Further, the polarization properties of scattered light from tissue contain wealth of morphological and functional information of potential biomedical importance. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 72 publications
(245 reference statements)
0
11
0
Order By: Relevance
“…19 Simulation and experimentation results validate that the proposed LSSDP outperforms than the PSIMSO and SPR in general. The work is expected to improve the image reconstruction quality for practical applications such as imaging through turbid media in biomedical, [22][23][24] and scattering property measurement of certain media, 24,25 such as fog and optical image encryption. 26,27 The rest of this paper is organized as follows: Sec.…”
Section: Introductionmentioning
confidence: 99%
“…19 Simulation and experimentation results validate that the proposed LSSDP outperforms than the PSIMSO and SPR in general. The work is expected to improve the image reconstruction quality for practical applications such as imaging through turbid media in biomedical, [22][23][24] and scattering property measurement of certain media, 24,25 such as fog and optical image encryption. 26,27 The rest of this paper is organized as follows: Sec.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the elastic scattering spectrum contains rich morphological information about the biological tissue samples due to the inhomogeneity of the constituent organelles' sizes. 8,14,[16][17][18][19][20][21][22][23][24][25][26][27][28] The angular and wavelength dependence of the elastic scattering spectra have been used to analyze such subtle variations in the morphological changes. 9,16,19,21,26,28 In this work, we perform a Monochromatic Transmission Imaging (MTI) of the tissue samples which provides us with small angle scattering information of the biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…1-5 Although polarimetry is well suited for applications in optically clear media and for studies of surfaces; recent studies have shown that by suitable modifications in measurement and analysis methods, it can be applied to the highly turbid media as well. 6 As is known, multiple scattering in optically thick turbid media such as polymer nanoparticles and most biological tissues causes extensive depolarization that confounds the established techniques. 2,3,6 There have been several attempts showing that polarization properties of fluorescence scattering may provide additional information.…”
mentioning
confidence: 99%
“…6 As is known, multiple scattering in optically thick turbid media such as polymer nanoparticles and most biological tissues causes extensive depolarization that confounds the established techniques. 2,3,6 There have been several attempts showing that polarization properties of fluorescence scattering may provide additional information. 7,8 However, these studies have considered similar approaches to the conventional measurements of the fluorescence polarization anisotropy, which is done using the linear polarization excitation only.…”
mentioning
confidence: 99%